Design and optimization of tocotrienol rich fraction nanoemulsion system for cosmeceutical application - Azizul Hasan, Zafarizal Aldrin (2018)
Highly stabilized nanoemulsion system requires high concentration of surfactant, high homogenization pressures and process cycles. However, the high surfactant concentrations may induce skin irritation while the high homogenization pressures and process cycles may incur higher operation cost. Another important problem is the absorption inefficiency of active such as tocotrienol rich fraction (TRF) into skin which affects product efficacy. This study aims to improve the stability of TRF nanoemulsion and effective absorption of TRF into skin by designing TRF nanoemulsion using Hansen Solubility Parameter (HSP) concept. The HSP concept allows alteration of the oil phase solubility which reduces Ostwald ripening and improves solubility of TRF into skin. TRF nanoemulsion was prepared by optimizing high shear homogenization conditions with pressure of 15,000 psi and minimum of 3 process cycles which yielded nanoemulsions of average droplet size of 137 ± 3 nm with zeta potential of -24.9 ± 2.2 mV and polydispersity index of 0.22. Nanoemulsions with less than 3% surfactant resulted in less significant droplet size reduction compared to nanoemulsion with more than 5% surfactant. From Stokes Equation, the velocity of TRF nanoemulsions with droplet size between 50 and 53 nm was calculated in the region of 10-15 m.s-1. Oswald Ripening, which is the main destabilization factor affecting nanoemulsion stability, was effectively reduced by increasing volume fraction of TRF to φ = 0.4 – 0.5 of the nanoemulsion disperse phase. The solubility gap based on HSP was higher at 2.46 - 3.12 indicating that the modified oil phase has lower solubility which inhibited Ostwald ripening. At these volume fractions, the system is approaching thermodynamic stability where Ostwald Ripening rate has plateau. Optimization of nanoemulsion with TRF in combination with glycerine and octocrylene was predicted and proven to have better delivery of TRF into skin compared to other combinations of TRF. The solubility gap based on HSP was lower at 4.2 indicating the oil phase has higher solubility into skin. The penetration profiles via tape stripping technique showed that optimized TRF nanoemulsion recorded highest TRF at 0.493 μg.cm-2. The steady-state flux proved that TRF nanoemulsion optimized with HSP concept delivered the highest average flux value (0.2556 μg/cm2.h), followed by the TRF nanoemulsion (0.1998 μg/cm2.h) and TRF Macroemulsion (0.1360 μg/cm2.h). This indicated that optimized TRF Nanoemulsion allows more TRF to permeate through the skin via passive diffusion. In vitro ocular and dermal irritection based on protein assays and in vitro ocular and dermal irritation using reconstructed human epidermis and human epithelial models showed that TRF nanoemulsions did not induce any ocular or dermal irritations. In vitro sun protection factor test and in vivo skin hydration showed that TRF nanoemulsion was having better UV protection and effective in maintaining higher level of skin hydration. This study has shown that stable TRF nanoemulsion with higher absorption of TRF into skin can be achieved by designing TRF nanoemulsion based on HSP concept.